Balancing - Portocarrero Quispe, Jorge Alexander (EUNOMÍA. Revista en Cultura de la Legalidad, 2017)
The term “balancing”, as it is the case of many words from the ordinary language, is an ambiguous term, i.e, this term is used by different speakers in different contexts with different meanings. Balancing could be understood in some contexts as the action of weighing interests or cost-benefits relationships, in some other contexts balancing is understood as a interpretative structure of legal principles. On this last meaning will turn the following considerations. The balancing is a methodological structure applied to justify conditional priority relations between colliding legal principles, i.e. norms whose legal command can be fulfil in grades. Applying balancing always depends on the circumstances of a case in which two or more legal principles are in conflict about which of them should be the suitable criteria to be used to solve the specific problematic of the case. The balancing must be understood just as an interpretative structure and not as a material criteria, since it is limited to put in a comparative relationship the arguments for and against the use of each the colliding legal principles involved in the case; the content and material value of these arguments are not given by the structure of the balancing but from the factual and legal circumstances of each case. The balancing consists of four argumentative stages: the law of balancing, the weight formula, the law of competing principles and the burden of argumentation (or prima facie priorities).doi: https://doi.org/10.20318/eunomia.2017.3653
Keywords: balancing; legal argumentation; theory of principles; constitutional rights; constitutional interpretation; formal principles